METODE FORWARD CHAINING DALAM PENENTUAN CALON LEGISLATIF PARTAI POLITIK - mhd ali (Politeknik Bisnis Indonesia, 2018)
This Research is designed for an method system in the form of expert system applications to present information on Determination Legislative Candidates. The purpose of this system is to help determine the candidates of political parties in the party prosperous justice in particular, generally all political parties in Indonesia for the needs of the community. This system presents the determination of candidates in the form of membership diagnosis cadres and social community. The analysis is done by determining in advance the rule, and then do a goal to obtain the desired information. The design of this system using Forward Chaining method with system implementation using My-SQL database system and programming language PHP. The system is web-based, so it can be accessed by using a computer